2018
DOI: 10.1101/374181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-occurring alterations in the RAS-MAPK pathway limit response to MET inhibitor treatment inMETexon 14 skipping mutation positive lung cancer

Abstract: Abstract:While patients with advanced-stage non-small cell lung cancers (NSCLCs) harboring MET exon 14 skipping mutations (METex14) often benefit from MET tyrosine kinase inhibitor (TKI) treatment, their long-term survival is limited by drug resistance. The molecular basis for this resistance remains incompletely understood. Through targeted sequencing analysis of cell-free circulating tumor DNA obtained from 289 patients with advanced-stage METex14 NSCLC, we find prominent co-occurring RAS pathway gene altera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…Recent studies showed that advanced‐stage NSCLCs often harboured multiple oncogenic alterations, which may impact its response to targeted therapies 7,31,32 . In METex14 , co‐occurring gene alterations in the phosphatidylinositol‐3‐kinase (PI3K) or RAS–mitogen‐activated protein kinase (RAS–MAPK) pathway have been shown in NSCLCs 33,34 . In the present cohort of surgically resected cases, concurrent METex14/PIK3CA mutations were detected in minimally invasive adenocarcinoma.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies showed that advanced‐stage NSCLCs often harboured multiple oncogenic alterations, which may impact its response to targeted therapies 7,31,32 . In METex14 , co‐occurring gene alterations in the phosphatidylinositol‐3‐kinase (PI3K) or RAS–mitogen‐activated protein kinase (RAS–MAPK) pathway have been shown in NSCLCs 33,34 . In the present cohort of surgically resected cases, concurrent METex14/PIK3CA mutations were detected in minimally invasive adenocarcinoma.…”
Section: Discussionmentioning
confidence: 62%
“…4a, b). C-MET (mesenchymal-epithelial transition factor/scatter factor receptor), which ligand is HGF/SF (ligand hepatocyte growth factor/scatter factor), can trigger various of downstream signaling pathways, such as PI3K/AKT, JAK/STAT, Ras/MAPK, and GSK3β/β-catenin [28][29][30]. The question arises as to how TMEM220 inhibits the activation of c-MET.…”
Section: Discussionmentioning
confidence: 99%
“…and clinical data have demonstrated that tumors harboring METex14 skipping alterations along with other mutations, RAS-MAPK or PI3K/AKT pathway mutations, show reduced response to MET TKIs. [162][163][164] Overall, the resistance mechanisms against different types of MET inhibitor can be different. 109 Therapy combining relevant inhibitors can be helpful for the treatment of NSCLC with METex14 skipping alteration along with other driver mutations.…”
Section: Review Lung Cancermentioning
confidence: 99%
“…109 Therapy combining relevant inhibitors can be helpful for the treatment of NSCLC with METex14 skipping alteration along with other driver mutations. 164,165 Extensive studies are needed to unravel the full spectrum of resistance mechanisms against the inhibitor drugs for optimising therapeutic intervention.…”
Section: Review Lung Cancermentioning
confidence: 99%